Preprocedural Ultrasound for Infant Lumbar Puncture: A Randomized Clinical Trial. (16th May 2018) - Kessler, David; Pahalyants, Vartan; Kriger, Joshua; Behr, Gerald; Dayan, Peter
Abstract: Background: Our purpose was to determine the potential effect of preprocedural ultrasound (US) to increase lumbar puncture (LP) success compared with standard palpation method. Further, we assessed feasibility of and clinician satisfaction with a standardized US protocol. Methods: This prospective, two‐arm, parallel‐group randomized trial was conducted in a single‐center pediatric emergency department. We compared preprocedural US versus palpation method on success with infant LPs. Infants less than 3 months of age requiring LP were enrolled. Sixteen pediatric emergency medicine physicians with varied US experience were trained to conduct the USs to mark interspace locations. Primary outcome was successful LP, defined as obtaining a cerebrospinal fluid (CSF) sample on first attempt with < 1, 000 red blood cells per high‐powered field (clear CSF). Secondary outcomes included clear CSF on any attempt, any CSF on the first attempt, traumatic LP proportion, and LP attempt frequency. Feasibility was assessed by comparing provider number attempting the LP and procedure duration. Clinician satisfaction and sonographer perceptions of US acceptability and impact were assessed. Results: Eighty‐one patients consented and 80 were analyzed (99%): 40 per group. No statistical difference was seen for the primary outcome (p > 0.05) between intervention and control groups (difference 3%; 95% confidence interval = –19% to 24%). There were no statistical differences between intervention and controls groups for secondary outcomes including the rate of traumatic LPs, number of attempts, and the duration of LP procedure. Most sonographers (84%) strongly agreed or agreed that the US protocol was technically easy to perform, well tolerated by the patient (94%), well accepted by the family (100%), and well accepted by the LP procedural clinicians (99%). In the US group, the majority of clinicians who performed the LPs (68.4%) noted that the preprocedural US influenced their behavior, most commonly helping with overall visualization at the selected interspace (28.9%) or prompting a change in interspace (26.3% higher, 5.3% lower). Seventy‐seven percent agreed or strongly agreed that they would like to use the technique again for their next LP. The mean US duration was 4.6 minutes. Conclusions: Preprocedural US by did not improve the rates of first‐attempt success when compared with palpation method. Our results suggest that US is feasible and well accepted, with a perceptible impact on care.